2020
DOI: 10.1111/cdoe.12584
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms of exposure to substances in the workplace among Bulgarian dentists

Abstract: Objectives Dentists are exposed to a variety of airborne chemicals that can act as irritants and sensitizers and may give rise to work‐related respiratory symptoms. The aim of this study was to estimate the prevalence of respiratory symptoms of exposure to substances in the workplace and associated risk factors in Bulgarian dentists. Methods A cross‐sectional study was performed among Bulgarian dentists by using a self‐report questionnaire. A direct acyclic graph (DAG) was elaborated to illustrate the direct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Showed that 2 % glutaraldehyde showed a reduction of 4 log10 in 28 samples studied, demonstrating effectiveness of 10 0 %, the effectiveness of glutaraldehyde where we see that in five of the samples the effectiveness of glutaraldehyde was reduced to 0 in the number of CFU/mL, while four of them had different bacterial count [ 28 ]. When analyzing the colonies of the petri dishes, a Gram stain was performed, a sporulated microorganism was found and hence the resistance of this species to the effect of the disinfectant; the microorganism was identified as Bacillus spp [ 29 ], indicating that no disinfectant spray was effective against it [ 30 ], confirm that a combination of sodium hypochlorite and hydrogen peroxide (OX-B7) is capable of effectively killing Bacillus subtillis spores on both porous and non-porous surfaces [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Showed that 2 % glutaraldehyde showed a reduction of 4 log10 in 28 samples studied, demonstrating effectiveness of 10 0 %, the effectiveness of glutaraldehyde where we see that in five of the samples the effectiveness of glutaraldehyde was reduced to 0 in the number of CFU/mL, while four of them had different bacterial count [ 28 ]. When analyzing the colonies of the petri dishes, a Gram stain was performed, a sporulated microorganism was found and hence the resistance of this species to the effect of the disinfectant; the microorganism was identified as Bacillus spp [ 29 ], indicating that no disinfectant spray was effective against it [ 30 ], confirm that a combination of sodium hypochlorite and hydrogen peroxide (OX-B7) is capable of effectively killing Bacillus subtillis spores on both porous and non-porous surfaces [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater odds of respiratory symptoms for those with greater years of work experience have been observed in multiple studies ( Gonzalez et al 2014 ; Patel et al 2020 ; Stoeva 2021 ). These data provide some insights into potential latency durations, but the studies do not have data about the periods or duration of exposure across HCWs’ careers.…”
Section: Resultsmentioning
confidence: 81%
“…In a study of dentists, the most commonly reported (65.7%) cause of respiratory reactions was disinfectants, and greater years of work experience was an identified risk factor, where those with 11–20 years of experience had 1.45 OR (95% CI: 1.13–.86) and those with >20 years of experience had 2.19 (95% CI: 1.78–2.70) greater odds of respiratory symptoms than those with less than five years of experience ( Stoeva 2021 ). Among those who reported respiratory symptoms, the greatest proportions of reported respiratory symptom onset were for 2–5 years after graduation (33.2%, 72/217 of men with respiratory symptoms) and 6–10 years after graduation (18.6%, 140/752 of women) ( Stoeva 2021 ). In a study of certified nursing assistants (CNAs), those with 17–26 years at the job had 2.83 (95% CI: 1.24, 6.48) greater odds of bronchial hyper responsiveness (BHR) symptoms than those with 0–9 years at the job ( Patel et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Long-term exposure to dental dust is likely to trigger a variety of respiratory symptoms, including cough, nasal symptoms (runny nose or blocked or sneezing), pharyngitis, dyspnea, and hoarseness. Stoeva et al conducted cross-sectional research among 4,675 dentists and found a 20.7% prevalence of work-related respiratory symptoms, which were associated with a lengthy period of employment, a history of atopic illness, and the female gender [ 30 ]. And a Finnish study reported that the prevalence of occupational-related respiratory symptoms among orthodontists ( n = 141) and general dental practitioners ( n = 208) was 28% and 18%, respectively [ 31 ].…”
Section: Dust-related Respiratory Diseases Of Dental Professionalsmentioning
confidence: 99%